2019
DOI: 10.1177/0013916518824376
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to Act for the Protection of Nature Biodiversity and the Environment: A Matter of “Significance”

Abstract: Environmental activism, defined as a range of difficult pro-environmental behaviors, is analyzed within the conceptual framework of Significance Quest Theory (SQT). In Study 1, 40 interviews were carried out on two groups of people in the European Union: Committed Actors for Nature (CANs, n = 25) versus Committed Actors for Society (CASs, n = 15). Results demonstrated that Significance Quest (SQ) motivates each group to be strongly committed to their chosen action and the main difference between them being in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
(83 reference statements)
0
32
0
Order By: Relevance
“…A similar pattern emerged in qualitative interviews with environmental activists, in which the desire for significance was shown to underlie these individuals' commitment to self-sacrificial proenvironmental actions (i.e., protecting nature and biodiversity; Molinario et al, 2018). After answering questions measuring their sense of personal significance and meaning in life, participants indicated their willingness to engage in easy (e.g., recycling) or difficult (e.g., volunteering for wildlife conservation) proenvironmental behaviors.…”
Section: Quest For Significance and Peaceful Extremismmentioning
confidence: 64%
“…A similar pattern emerged in qualitative interviews with environmental activists, in which the desire for significance was shown to underlie these individuals' commitment to self-sacrificial proenvironmental actions (i.e., protecting nature and biodiversity; Molinario et al, 2018). After answering questions measuring their sense of personal significance and meaning in life, participants indicated their willingness to engage in easy (e.g., recycling) or difficult (e.g., volunteering for wildlife conservation) proenvironmental behaviors.…”
Section: Quest For Significance and Peaceful Extremismmentioning
confidence: 64%
“…A variety of studies have highlighted how volunteers and activists in conservation are not only motivated by the urge to protect nature but also by motivations related to living a meaningful life and strengthening relationships with human and more-than-human others (Admiraal et al 2017;Molinario et al 2019). Through this bonding, volunteers increasingly identify with specific landscapes or green areas, which is in turn an important motivation to become more active in local volunteering activities (Pagès et al 2018;Schild 2018).…”
Section: Relational Values and People's Action For Naturementioning
confidence: 99%
“…For example, according to self‐affirmation theory (Steele, ), engagement in activities that remind people of who they are and enable them to express personally important values leads to increased self‐esteem (e.g., Cohen, Aronson, & Steele, ; Fein & Spencer, ). Recent research showed that acting for important values (e.g., pro‐environmental values) makes people feel more meaningful and fulfilled (Molinario et al., ). Also, in the context of political activism, Skitka, Hanson, and Wisneski () showed that higher levels of moral convictions associated with issues of same‐sex marriage and permission to carry guns on college campuses were related to stronger anticipated feelings of pride.…”
Section: Activism As a Reaction To Negative Experiencesmentioning
confidence: 99%